2010
DOI: 10.1038/ismej.2010.164
|View full text |Cite
|
Sign up to set email alerts
|

Composition, uniqueness and variability of the epiphytic bacterial community of the green alga Ulva australis

Abstract: Green Ulvacean marine macroalgae are distributed worldwide in coastal tidal and subtidal ecosystems. As for many living surfaces in the marine environment, little is known concerning the epiphytic bacterial biofilm communities that inhabit algal surfaces. This study reports on the largest published libraries of near full-length 16S rRNA genes from a marine algal surface (5293 sequences from six samples) allowing for an in-depth assessment of the diversity and phylogenetic profile of the bacterial community on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
324
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(378 citation statements)
references
References 84 publications
(98 reference statements)
37
324
5
2
Order By: Relevance
“…This model of community assembly is assumed in the neutral theory (Hubbell, 2001), which has successfully predicted species distribution curves for communities of macroscopic organisms (Hubbell, 2005) as well as microbial communities (Sloan et al, 2006). Similar observations indicating a high variability of bacterial OTUs between host individuals have also been reported for the green seaweed Ulva australis (Burke et al, 2011b), suggesting that seaweeds (including both kelps and green algae such as Ulva) display common patterns of surface bacterial community assembly. In the case of U. australis, it was recently shown that this lack of phylogenetic similarity (inferred by 16S rRNA gene sequences) is contrasted by a high similarity of functional genes (Burke et al, 2011a).…”
Section: Mechanisms Of Community Assemblymentioning
confidence: 49%
“…This model of community assembly is assumed in the neutral theory (Hubbell, 2001), which has successfully predicted species distribution curves for communities of macroscopic organisms (Hubbell, 2005) as well as microbial communities (Sloan et al, 2006). Similar observations indicating a high variability of bacterial OTUs between host individuals have also been reported for the green seaweed Ulva australis (Burke et al, 2011b), suggesting that seaweeds (including both kelps and green algae such as Ulva) display common patterns of surface bacterial community assembly. In the case of U. australis, it was recently shown that this lack of phylogenetic similarity (inferred by 16S rRNA gene sequences) is contrasted by a high similarity of functional genes (Burke et al, 2011a).…”
Section: Mechanisms Of Community Assemblymentioning
confidence: 49%
“…The colonisation process itself could be most likely explained by the competitive lottery model as already proposed for the colonisation of algal surfaces (Burke et al 2011b). In this context, we suggest to investigate the link between community structure and function using metagenomic sequence analysis (Burke et al 2011a) in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that examining assembly processes using metagenomics or metatranscriptomics would reveal different patterns in the relative importance of niche vs neutral processes. For example, Burke et al (2011) recently showed that microbial community succession on marine algae displayed functional convergence but Figure 3 The three hypothesized phases of community assembly following disturbance. Phase 1 is characterized by more neutral assembly processes; Phase 2 is more niche-based and Phase 3 is increasingly more neutral.…”
Section: Discussionmentioning
confidence: 99%